KENCENDERUNGAN PUTUSAN-PUTUSAN HAKIM PENGADILAN TERHADAP PENCANTUMAN KLAUSULA EKSONERASI DALAM PERJANJIAN - Cherdina Efenti; Runtung Runtung; Bismar Nasution; Mahmul Siregar (Universitas Sumatera Utara, 2015)
ABSTRACT The scope of the prohibition to attach exoneration clause in a standard agreement is not found in the Civil Code; it is found in Article 18, paragraph 1 of UUPK. The attachment of exoneration clause is contrary to the sense of righteousness if it is viewed from distributive fairness theory and to the principles of adequacy, harmony, fairness, and naturalness although it is in line with commutative righteousness theory. The inclination of seven judges’ verdicts does not directly consider exoneration clause but tends to see the validity of the contract according to Article 1320 of the Civil Code and Article 1338 of the Civil Code.It is recommended that Article 18, paragraph 1 of UUPK should be confirmed as exoneration clause or exoneration clause in its explanation. Besides that, the panel of judges should not be too rigid in interpreting righteousness and the principle of consensus; they should be open widely to interpret law from concrete occurrence, concerning the validity of a contract according to Article 1339 of the Civil Code. Keywords : Inclination, Judges’ Verdicts, Standard Clause, Exoneration Clause, Agreement